Respons Pertumbuhan Dan Produksi Dua Varietas Selada (Lactuca Sativa L.) Terhadap Pemberian Berbagai Sumber Nitrogen - Jepriwira K. Ginting; Jonis Ginting; Nini Rahmawati (Talenta Publisher, 2018)
The research aims to determine the growth and production response of two varieties of lettuce (Lactuca sativa L.) to the provision of various sources of nitrogen. This research was conducted in Lambar village, Tigapanah sub-district, Karo regency, Sumatera Utara Province with altitude of ± 1200 meters above sea level, which started on July to September 2017. This research used a factorial randomized block design with 2 factors namely varieties of lettuce (crop and lettuce) and sources of nitrogen (urea fertilizer, chicken manure and Liquid organic fertilizer of rabbit urine). The parameters observed were plant height, greenish leaves, crop circle, fresh weight of plant per sample and fresh weight of plant per plot. The results showed that both varieties were significantly different in the parameters of plant height, greenish leaves, the number of leaves, and the fresh weight of the plant per sample. Application of nitrogen source showed differences in plant height at 10 weeks after move planting and fresh weight of plant per sample.